Supply chain design considering correlated failures and inspection in pharmaceutical and food supply chains. (September 2017) - Pariazar, Mahmood; Root, Sarah; Sir, Mustafa Y.
Highlights: Supply chain design is studied considering correlated failures and inspection. Supplier correlation and inspection effects are examined on supply chain design. Inspection is recommended to prevent shipping damaged goods. Correlated supplier failures increase total cost and affect network design. Redundant capacity and inspection are critical to reduce costs and supply shortages. Abstract: This paper studies the impact of correlated supplier failures as well as inspection to detect these failures in the context of a supplier selection problem. A two-stage stochastic programming model is developed to explore the tradeoffs between costs and risk when designing a supply network. The first-stage decisions include the strategic decisions of determining which suppliers should be selected considering suppliers location and capacity while in the second stage, operational decisions related to transportation and inspection are determined. Several computational results are presented examining the effect of supplier correlation and inspection on supplier selection, transportation, and inspection strategies. A sensitivity analysis is also performed to explain the effect of key parameters on expected total cost and expected cost of shipped tainted materials.